Coronal Vertebral Clefts: A Radiological Indicator for Chromosomal Aberrations. (January 2013) - Doberentz, Elke; Schumacher, Reinhard; Gembruch, Ulrich; Gasser, Jürg Andreas; Müller, Annette M.
Coronal clefts—a radiolucent band running through at least one vertebral body, visualized in the lateral spinal radiograph and discussed as a physiological variation of the fetal vertebral ossification pattern—are often found in fetal autopsies with trisomies. Published studies are missing concerning the question of whether this finding could serve as a diagnostic radiological or even ultrasonographic sign. We studied the incidence of radiological coronal clefts and their association with chromosomal aberrations in 443 fetuses (mostly medically induced abortions). In 42 of the 443 fetuses (9.5%), coronal clefts were visualized. The majority (71%) were localized in the lumbar spine. No cervical or singular sacral clefts were detected. Twenty-five of the 42 fetuses (60%) displaying coronal clefts had chromosomal aberrations, either as a trisomy (13 or 21) or as monosomy X. Histologically, coronal clefts showed a missing central ossification of the vertebral body. Remnants of the notochord could be excluded. Hence, coronal clefts represent a variant ossification of vertebral bodies in fetal development that is found almost exclusively in fetuses with chromosomal aberrations or severe congenital malformations. This finding could be a helpful supplement to prenatal diagnostics and fetal autopsy. On the other hand, the genetic diagnosis of chromosomal aberration, especially trisomy, does not automatically imply the presence of coronal clefts.